2017
DOI: 10.1097/md.0000000000006356
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of contact dermatitis among clothing manufacturing employees in Beijing

Abstract: Little is known about the epidemiology of contact dermatitis (CD) in the Chinese clothing industry. This study aimed to investigate the prevalence and some risk factors of contact dermatitis among clothing manufacturing employees in Beijing.This cross-sectional study was conducted by interview using self-administered questionnaires and skin examination between May and August in 2016. Five-hundred twenty-nine employees who had worked at sewing, ironing, and as managers at 12 clothing manufacturing factories wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
24
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 30 publications
6
24
2
1
Order By: Relevance
“…X. This result is the same with the study conducted by Chen et al, 18 in clothing manufacturing workers in Beijing, China. The study found a significant risk of contact dermatitis among workers with allergic rhinitis (OR= 2.3, 95% CI= 1.12-4.55).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…X. This result is the same with the study conducted by Chen et al, 18 in clothing manufacturing workers in Beijing, China. The study found a significant risk of contact dermatitis among workers with allergic rhinitis (OR= 2.3, 95% CI= 1.12-4.55).…”
Section: Discussionsupporting
confidence: 89%
“…The study found a significant risk of contact dermatitis among workers with allergic rhinitis (OR= 2.3, 95% CI= 1.12-4.55). 18 Wearing gloves during work is a factor that contributes considerably to WRSDs among sewing workers at PT. X.…”
Section: Discussionmentioning
confidence: 99%
“…Textile workers are frequently exposed many potentially harmful substances, such as metal tools, dyes, potassium dichromate, leather, aerosols, adhesives, and finishing agents. [8,17,21] OACD in textile workers is most often attributed to sensitization to textile/formaldehyde resins and disperse dyes/dye finishes, which are typically used to color mixed fabrics/fibers. [8,22] Lisi et al [23] stated that the prevalence of OACD caused by textile dyes ranged from 1.4% to 5.8%.…”
Section: Discussionmentioning
confidence: 99%
“…[.1] Contact dermatitis is an important health problem in occupations, affects mostly manual work, and is usually described as a skin reaction caused by frequent contact with irritants or allergens. [2] Hand contact dermatitis forms about 90-95% of occupational skin diseases. It could be allergic or irritant.…”
Section: Introductionmentioning
confidence: 99%